AB0423 Nobility, A Phase 2 Trial To Assess The Safety and Efficacy of Obinutuzumab, A Novel Type 2 Anti-CD20 Monoclonal Antibody (MAB), in Patients (PTS) with ISN/RPS Class III or IV Lupus Nephritis (LN). (15th July 2016) - Schindler, T.; Rovin, B.; Furie, R.; Leandro, M.; Clark, M.; Brunetta, P.; Garg, J.
Abstract : Background: B cells infiltrate the kidneys of LN pts, and leukocyte-rich tubulointerstitial infiltrates are associated with greater risk for progression to renal failure. High-sensitivity flow cytometry (HSFC) analysis suggests incomplete B-cell depletion in systemic lupus erythematosus (SLE) is associated with nonresponse to rituximab (RTX). Obinutuzumab (Obi) is a glycoengineered type 2 anti-CD20 mAb that binds CD20 differently from RTX, a conventional type 1 anti-CD20 mAb, and depletes B cells to a greater degree than RTX. In preclinical studies, Obi displayed significantly increased antibody-dependent cellular cytotoxicity and enhanced direct cell death over type 1 anti-CD20 mAbs. In the CLL11 trial, which led to FDA breakthrough designation and its licensing in chronic lymphocytic leukemia, Obi demonstrated greater progression-free survival and greater minimal residual disease negativity over RTX even in protected microenvironments such as bone marrow. Double-blind randomized controlled trials demonstrated that type 1 anti-CD20 mAbs added to mycophenolate mofetil (MMF) or cyclophosphamide (CYC) increased the proportions of pts achieving partial renal response (PRR) but had no impact on complete renal response (CRR) rates at 12 months. Although these studies with RTX and ocrelizumab did not meet their respective primary endpoints, EULAR and ACR LN guidelines recommend RTX if treatment with CYC or MMF fails. Objectives: The phase 2 study NOBILITY is designed to test the hypothesis that Obi may generate superior CRR rates in pts with active proliferative LN based on its ability to deplete B cells to a greater degree than type 1 anti-CD20 mAbs. The primary objective of this study is to evaluate the effect of Obi compared with placebo (PBO) when added to MMF in pts with class III or IV LN as assessed by the proportion of pts who achieve CRR at wk 52. Key secondary objectives relate to overall response (CRR + PRR), PRR, change in biomarkers of LN disease activity, and time to CRR. Methods: Randomized, double-blind, PBO-controlled study to evaluate safety and efficacy of Obi added to MMF and corticosteroids (CS) in pts with ISN/RPS 2003 class III or IV LN. Results: The study design is as follows: NOBILITY is a global multicenter study enrolling ∼120 pts with biopsy-proven ISN/RPS 2003 class III or IV LN in the United States, Mexico, Columbia, Argentina, Spain, Israel, Brazil, and France. All pts will be on MMF up to 2.5 g/d and a combination of IV and oral CS to be tapered to 7.5 mg/d by wk 12. All pts will be followed up until wk 104, with the primary endpoint evaluation at wk 52 (figure ). NOBILITY also features interim analyses at wk 4 for depletion of peripheral CD19 + B cells by HSFC, centralized evaluation of the renal biopsy, and repeat renal biopsy on the basis of clinical status and local practice. Conclusions: NOBILITY, a phase 2 trial evaluating Obi in LN, is grounded on the hypothesis that a type 2 anti-CD20 mAb will induce greater B-cell depletion in the kidneys and associated secondary lymphoid structures, translating to significant CRR rates. Disclosure of Interest: T. Schindler Employee of: F. Hoffmann-La Roche, B. Rovin Grant/research support from: Genentech, Consultant for: Genentech, R. Furie: None declared, M. Leandro Grant/research support from: Roche, Consultant for: Roche, Genentech, Chugai, Lilly, BMS, M. Clark Grant/research support from: AbbVie, Consultant for: Genentech, P. Brunetta Shareholder of: Genentech, Employee of: Genentech, J. Garg Shareholder of: Roche, Employee of: Genentech